THE LEGALITIES OF MANDATORY COVID-19 VACCINATION AT UNIVERSITIES: LESSONS TO BE LEARNT FROM Klaassen v Trustees of Indiana University (No. 1:21-CV-238 DRL, N.D. Ind.) - Desan Iyer (Obiter, 2022)
The Covid-19 pandemic, which started in Wuhan, China, in December 2019, has continued to wreak havoc and has changed humanity forever. The Higher Education sector, like many others, has not been spared. In an effort to save the academic year and ensure that some teaching and learning could take place in a safe and secure environment, many tertiary institutions in South Africa and other parts of the world transitioned to online education. There is no doubt that online learning promotes rich learning and understanding, and it is an effective modality for teaching both concepts and skills in most disciplines. Online education has enabled many tertiary institutions to become innovative in the way students learn and academics teach, while also overcoming the constraints of space, time and distance. However, the shift to remote learning has also unmasked historical, geospatial and economic inequalities that permeate the world in which students live. Challenges include the digital divide, lack of technical support, poor learning environments, conditions at home, and lack of assets (among others), resulting in many student organisations in Africa and South Africa rejecting online teaching, with some viewing it as “an unaffordable, impractical and an elitist solution” to COVID-19. With the realisation that COVID-19 is here to stay for a while, and many students complaining about the difficulties posed by online learning from home, it seems inevitable that many universities in South Africa have already or may in future consider expediting the return of students to campus. However, to open fully, universities (like other sectors) may deem it necessary, as part of their planning process, to make it mandatory for all staff and students to be vaccinated. The question that arises then is whether mandatory vaccination in a tertiary setting will pass constitutional muster in a court of law. Students, if required to vaccinate or produce a vaccination card upon entry to campus, may argue that their legal rights, such as their right to bodily integrity, religious freedom and possibly their choice to choose or refuse their medical treatment, may be infringed. South Africa has not yet had to deal with such challenges. However, the US case of Klaassen v Trustees of Indiana University (No 1:21-CV-238 DRL ND IND) (Klaassen) 1–101, was one of the first cases from a global perspective to deal with such challenges and can provide valuable assistance for South Africa going forward. This case note critically examines the case of Klaassen, which is a landmark case dealing with the issue of mandatory vaccinations for students within a university setting. It is hoped that the case will provide guidance to universities in drafting policy documents surrounding mandatory vaccination, as well as in dealing with possible legal challenges in future.